2019
DOI: 10.1515/dmpt-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

X-linked and autosomal dominant forms of the ichthyosis in coinheritance

Abstract: According to modern classification, there are two forms of inherited ichthyoses: syndromic and non-syndromic, each of them consists of more than ten different nosologies. The commonest types of the ichthyosis are X-linked recessive (prevalence 1/2000–6000 in men) and autosomal dominant, or ichthyosis vulgaris with incomplete penetrance (1/250–1000). The X-linked form is associated with mutations in steroid sulfatase STS gene, it is noteworthy that there is a full deletion of the gene in 90% of cases. Ichthyosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Among the documented FLG loss of function variants in our study, 20% of the variants were previously reported in European and Asian populations and 80% were unique variants. 16,17,19,20 India is home to more than 2000 ethnic populations, whose genetic origins are complex. The present Indian population is genetically heterogeneous with an admixture of ancestral north Indians comprising the majority and having roots in the Middle East, Central Asia and Europe and ancestral south Indians that have no relation to any population outside India.…”
Section: Molecular Resultsmentioning
confidence: 99%
“…Among the documented FLG loss of function variants in our study, 20% of the variants were previously reported in European and Asian populations and 80% were unique variants. 16,17,19,20 India is home to more than 2000 ethnic populations, whose genetic origins are complex. The present Indian population is genetically heterogeneous with an admixture of ancestral north Indians comprising the majority and having roots in the Middle East, Central Asia and Europe and ancestral south Indians that have no relation to any population outside India.…”
Section: Molecular Resultsmentioning
confidence: 99%
“…Such cases are not as rare as they may seem. For instance, we would like to refer to a case of the coinheritance of X-linked and dominant forms of ichthyosis [ 51 ]. This information may be valuable for genetic counseling because of similar clinical symptoms.…”
Section: Human Monogenic Diseases: Population Genetics Researchmentioning
confidence: 99%
“… 16 The frequency and type of these mutations vary among populations, and they all lead to loss of filaggrin expression. Another mutation, p. Arg2037Ter in the heterozygous condition was previously identified as pathogenic in databases 35 with a penetrance of 90%. This nonsense mutation introduces a premature stop codon in the transcript of the mutant at position 2037, resulting in a truncated protein.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…Ichthyosis vulgaris has also been presented with comorbidities such as x‐linked ichthyosis, 35 disseminated tinea, 50 palmoplantar pustulosis (PPP), 51 and acute intermittent porphyria 52 . However, the association between ichthyosis vulgaris and any of these diseases has not been proved and could be a coincidence.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation